Steam explosion pretreatment enhancing enzymatic digestibility of overground tubers of tiger nut (Cyperus esculentus L.) - Zhao, Zhi-Min; Yu, Wenqing; Huang, Caitong; Xue, Huiting; Li, Juan; Zhang, Dejian; Li, Guanhua (Frontiers in Nutrition, 2023)
Tiger nut (TN) is recognized as a high potential plant which can grow in well-drained sandy or loamy soils and provide food nutrients. However, the overground tubers of TN remain unutilized currently, which limits the value-added utilization and large-area cultivation of this plant. In the present study, the overground tubers of TN were subjected to enzymatic hydrolysis to produce fermentable sugars for biofuels production. Steam explosion (SE) was applied to modify the physical-chemical properties of the overground tubers of TN for enhancing its saccharification. Results showed that SE broke the linkages of hemicellulose and lignin in the TN substrates and increased cellulose content through removal of hemicellulose. Meanwhile, SE cleaved inner linkages within cellulose molecules, reducing the degree of polymerization by 32.13% to 77.84%. Cellulose accessibility was significantly improved after SE, which was revealed visibly by the confocal laser scanning microscopy imaging techniques. As a result, enzymatic digestibility of the overground tubers of TN was dramatically enhanced. The cellulose conversion of the SE treated TN substrates reached 38.18% to 63.97%, which was 2.5 to 4.2 times higher than that without a SE treatment. Therefore, SE pretreatment promoted saccharification of the overground tubers of TN, which paves the way for value-added valorization of the TN plants.